Polypoid Lesions of the Gallbladder: A Five-Year Retrospective Study of Cholecystectomy Specimens - Shrivastav, Shreya; Shrestha, Susan Man; K.C., Bibek; Pradhan, Sumita (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Polypoid lesions of gallbladder (PLG) are a diverse group of disease ranging from inflammatory to malignant pathology. Their understanding and characterization clinically and pathologically would help in decision making regarding their management. Methods: A retrospective analytic study was conducted at the Department of Pathology between April 15th 2019 to April 14th 2025. We studied the histopathology reports of all cholecystectomies done in that period to determine the frequency and types of PLGs. A comparison of clinicopathological characteristics such as age of patient, site of polyp, whether the lesions were single or multiple was done. ROC analysis was done to establish a size cut off to differentiate neoplastic from non-neoplastic polyps. Results: We received 2134 cholecystectomy specimen of which 72 (3.4%) had polypoid lesions of gallbladder. There was a female preponderance (61%).Neoplastic polyps (n=44, 61%) were more common than non-neoplastic polyps. Among neoplastic polyps, 26 were benign and 18 were malignant The ROC analysis recognized an ideal cutoff of 9mm at which the sensitivity and specificity of detection of malignancy is 68.2% and 89.3% respectively (AUC = 0.862). Conclusion: Polypoid lesions of the gallbladder were encountered in 72 (3.4%) of all cholecystectomy specimens. Age of more than 50 years and size of 9mm are the most useful features to distinguish neoplastic from non-neoplastic from lesion. Malignant polypoid lesion of gallbladder tends to present late in our population.